Drug-Related Problems in Patients with Liver Failure: An Analysis of Pharmacokinetic Interactions and Dosing Inappropriateness A Literature Review - Nasution, Izza Aulia Rizqika; Reza Laila Najmi; Resi Rizki Banjarani; Sari Rahmadhani; Restu Anisa Puteri (The Journal Of Pharmacy, 2026)
Drug-related problems represent a major challenge in the pharmacotherapeutic management of patients with liver failure due to significant pharmacokinetic alterations, polypharmacy, and inappropriate dosing. Hepatic dysfunction affects drug absorption, distribution, metabolism, and elimination, thereby increasing the risk of adverse drug reactions, clinically significant drug–drug interactions, and therapeutic failure. This review aimed to summarize current evidence on the determinants of DRPs in patients with liver failure, focusing on pharmacokinetic changes, dose individualization, polypharmacy, and medication safety. A comprehensive literature review was conducted using PubMed, Embase, and the Cochrane Library to identify peer-reviewed studies published between 2015-2026. Keywords included liver failure, liver cirrhosis, drug-related problems, pharmacokinetics, dose adjustment, polypharmacy, and hepatic impairment. Eligible studies evaluated pharmacokinetic alterations, prescribing practices, medication safety, or clinical outcomes in adults with chronic liver disease. The findings consistently showed a high prevalence of DRPs in this population. Approximately one-quarter of commonly used medications required dose adjustment due to altered systemic exposure, while polypharmacy affected nearly one-third of patients and exceeded 50% in several cohorts. Inappropriate prescribing, inadequate dose individualization, and limited use of pharmacokinetic modeling were identified as major contributors to adverse drug reactions, hepatotoxicity, and clinically relevant drug–drug interactions. Additionally, reliance on conventional liver disease classification systems without integrating dynamic hepatic function markers often resulted in suboptimal therapy. Overall, pharmacokinetic alterations, polypharmacy, and inappropriate prescribing are key determinants of DRPs in patients with liver failure, underscoring the importance of individualized dosing, comprehensive medication review, pharmacokinetic modeling, and multidisciplinary pharmaceutical care to improve medication safety.